2002
DOI: 10.1038/sj.leu.2402416
|View full text |Cite
|
Sign up to set email alerts
|

MCL1 provides a window on the role of the BCL2 family in cell proliferation, differentiation and tumorigenesis

Abstract: The MCL1 gene (myeloid cell leukemia-1) was discovered serendipitously about a decade ago and proved to be a member of the emerging BCL2 gene family. Ongoing studies of this gene provide an interesting perspective on the role of the BCL2 family in transitions in cell phenotype. Specifically, gene products that influence cell viability as a major effect (eg MCL1, BCL2 and other family members) can act as key determinants in cell proliferation, differentiation and tumorigenesis. Although they do not have a direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
246
1
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 251 publications
(257 citation statements)
references
References 112 publications
8
246
1
2
Order By: Relevance
“…Expression of the pro-survival gene Mcl1, a member of the BCL2 family and a crucial regulator of HSC survival, has been implicated in the pathogenesis of AML. 33,34 Recent studies have shown that MCL1 contributes to chemoresistance and disease relapse. 35,36 FLT3 ITD has been shown to stimulate MCL1 expression in HSCs and LICs via the STAT5-dependent signaling pathway.…”
Section: Resultsmentioning
confidence: 99%
“…Expression of the pro-survival gene Mcl1, a member of the BCL2 family and a crucial regulator of HSC survival, has been implicated in the pathogenesis of AML. 33,34 Recent studies have shown that MCL1 contributes to chemoresistance and disease relapse. 35,36 FLT3 ITD has been shown to stimulate MCL1 expression in HSCs and LICs via the STAT5-dependent signaling pathway.…”
Section: Resultsmentioning
confidence: 99%
“…From these results, we suggest endogenous IL-6 as a survival factor in our cellular model. Mcl-1, which is highly expressed in hematopoietic cells, is an antiapoptotic member of the Bcl-2 family (Craig, 2002). In multiple myeloma (MM) cells, in which IL-6 plays a critical role in proliferation and survival, upregulation of Mcl-1 was shown to mediate the antiapoptotic effect of IL-6 (Jourdan et al, 2003), whereas the downregulation of the gene by antisense technology led to apoptosis (Derenne et al, 2002;Zhang et al, 2002;Le Gouill et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…We previously demonstrated that LNCaP-IL-6 Ć¾ cells lack the proapoptotic Bax and overexpress the antiapoptotic Bcl-2 proteins compared to the control cells (Steiner et al, 2006). We here considered another important regulator of apoptosis, myeloid cell leukemia 1 (Mcl-1) , originally identified as an early gene induced during differentiation of ML-1 myeloid leukemia cells (Kozopas et al, 1993;Craig, 2002). Mcl-1's role in the regulation of cell death has been mostly investigated in myeloma cells in which it mediates the prosurvival action of IL-6 (Jourdan et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…MAP kinases, PI3K/Akt, and JAK/ STAT). 6 Furthermore, like Bcl-X, Mcl-1 has been shown to be post-transcriptionally regulated through alternative splicing to form a proapoptotic molecule (MCL-1 S ) made up of exons 1 and 3. 6 MCL-1 is also regulated by phosphorylation in response to a variety of cell stimuli.…”
mentioning
confidence: 99%